2023
DOI: 10.1021/acsami.2c20502
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Catalytic Enzymes with n-Type Polymers for High-Performance Metabolite Sensors

Abstract: The tight regulation of the glucose concentration in the body is crucial for balanced physiological function. We developed an electrochemical transistor comprising an n-type conjugated polymer film in contact with a catalytic enzyme for sensitive and selective glucose detection in bodily fluids. Despite the promise of these sensors, the property of the polymer that led to such high performance has remained unknown, with charge transport being the only characteristic under focus. Here, we studied the impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Such a capacitance‐dependent change in the transfer characteristics is expected, [ 6 ] and it is the basis of OECT‐based biosensing, for example, in metabolite sensors. [ 39 ] Subsequently, we investigated the EEC‐induced shift in the threshold/turn‐off voltage in Figure S4c–e (Supporting Information) for devices with a small, medium, and large gate, respectively. All devices show a significant shift with increasing V ds , ranging from 854 (small gate) to 735 (medium gate) to 657 mV V ‐1 (large gate).…”
Section: Resultsmentioning
confidence: 99%
“…Such a capacitance‐dependent change in the transfer characteristics is expected, [ 6 ] and it is the basis of OECT‐based biosensing, for example, in metabolite sensors. [ 39 ] Subsequently, we investigated the EEC‐induced shift in the threshold/turn‐off voltage in Figure S4c–e (Supporting Information) for devices with a small, medium, and large gate, respectively. All devices show a significant shift with increasing V ds , ranging from 854 (small gate) to 735 (medium gate) to 657 mV V ‐1 (large gate).…”
Section: Resultsmentioning
confidence: 99%
“…When the surface carries a negative charge, it encourages the enzyme to adopt an optimal orientation for effective catalysis. 20 In addition, the potential of using enzymatic fuel cells for self-powered sensors was also explored. A glucose-fueled power supply was developed utilizing a GOx-adsorbed P-90 anode and an organic cathode p(EDOT- co -EDOTOH) (Fig.…”
Section: Applications Of N-type and Ambipolar Oectsmentioning
confidence: 99%
“…In recent years, there has been a growing focus on the application research of n-type materials and ambipolar materials. These include constructing complementary logic circuits, 16–18 enhanced electrophysiological recordings, 19 high-sensitivity electrochemical biosensing, 20–22 and versatile neuromorphic simulation 23 (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…To enhance glucose sensitivity, Ohayon et al employed multiphoton lithography to 3D-print oxygen-sensitive materials encapsulating glucose oxidase (GOx). 76 In the study of OECTs, Torricelli and colleagues conducted a comprehensive investigation into the ionic-electronic interactions within these devices. They revealed that the measurements were comprehensively explained by the electrostatic bulk uptake of ions within the OECTs, which neutralized both xed and mobile electronic charges.…”
Section: Bioelectronics For Biosensing Applicationsmentioning
confidence: 99%
“…To enhance glucose sensitivity, Ohayon et al employed multiphoton lithography to 3D-print oxygen-sensitive materials encapsulating glucose oxidase (GOx). 76…”
Section: Bioelectronics For Biosensing Applicationsmentioning
confidence: 99%